Degradation of Imidacloprid Residues on Unripe Tomatoes (Solanum lycopersicum) by AOPs and Its Analysis using Spectrophotometer and HPLC - Trisna Olinovela; Hazanita Jumiaty; Safni Safni; Syukri Syukri (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Imidacloprid is an insecticide-active ingredient used by farmers to kill and control insects. Imidacloprid residue can be found in unripe tomatoes. Consuming unripe tomatoes contaminated with imidacloprid can cause human health problems such as cancer, chronic kidney disease, neurological disorders, and reproductive issues. In this study, imidacloprid pesticide residues on unripe tomatoes were degraded by the Advanced Oxidation Processes (AOPs) method, namely ozonolysis, sonolysis, and sonozolysis at various processing times (5, 10, 15, 20, and 25 minutes) in 50 g sample mass and 100 mL water volume. The changes in imidacloprid concentration before and after degradation were measured using a UV-Vis spectrophotometer and HPLC. The results of imidacloprid residue degradation by sonolysis was 66.99%, ozonolysis was 74.87%, and sonozolysis was 66.00%. The degradation kinetics of the imidacloprid residue was then studied. Kinetic study of all AOPs methods found that imidacloprid degradation followed a first-order kinetic model. The kinetics data showed that ozonolysis degradation is faster than sonolysis and sonozolysis, with a half-life (t1/2) of 16.90 minutes.